Tactics on Corroborate Customer Intention by the Involvement of Influencer and E-WOM: A Case Study of Samsung Smartphone - Ida Ayu Iswari Pidada; Sheillania Sheillania (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study aims to analyze how influencers and e-WOM affect the purchase intention of Samsung smartphones in Denpasar, with brand awareness serving as a mediator. Data collection involved selecting 100 respondents who were interested in or already owned Samsung smartphones through purposive sampling. SmartPLS 4 was used to analyze the direct and indirect relationships between the variables. Research shows that brand awareness plays a role in connecting influencers, E-WOM, and purchase intention. This suggests that a higher level of brand awareness enhances consumers' willingness to purchase, supported by positive influencer engagement and e-WOM content. The findings highlight the significance of influencers and e-WOM in marketing plans, improving brand awareness and ultimately increasing purchase intent. This marketing strategy, driven by social factors, can help Samsung stay competitive in the domestic market.